ASONANSI DALAM CERPEN “UGD” KARYA DJENAR MAESA AYU - Nirmala, Afsun Aulia (Sasando, 2018)
The research that discusses about assonance can be related to literature including short stories. The "UGD" short story by Djenar Maesa Ayu is a work that contains some of the beauty of the language in it. Djenar is able to concoct language into a beautiful sentence. Thus this research is expected to be able to analyze the style of asonance in the "ER" short story. Asonansi is a vowel sound repetition to make internal rhymes in phrases or sentences, and together with alliteration and consonance function as one of the rhyme building blocks. Asonans do not have to rhyme; identity that depends only on the vowel and consonant sounds. Thus, asonance is the resemblance of units which are generally less than syllables. The method of this research is descriptive qualitative with the method of note and note. The results of this study were to describe the asonance in the ER short story by Djenar Maesa Ayu.